2016
DOI: 10.1016/j.jacc.2016.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure After Myocardial Infarction Is Associated With Increased Risk of Cancer

Abstract: Background Heart failure (HF) is associated with excess morbidity and mortality for which noncardiac causes are increasingly recognized. We previously described an increased risk of cancer among HF patients compared with community controls. Objectives In the present study, we examined whether HF was associated with an increased risk of subsequent cancer among a homogenous population of first myocardial infarction (MI) survivors. Methods A prospective cohort study was conducted among Olmsted County, Minneso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
91
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(98 citation statements)
references
References 27 publications
4
91
1
2
Order By: Relevance
“…Based on our data, it is, however, difficult to explain the exact mechanism(s) why the association became insignificant after adjustment for comorbidities, but it may be speculated that environmental factors like tobacco and alcohol [ 25 ], unhealthy diet, shared genetic susceptibility, inflammation [ 26 , 27 ] and medication play a role, since these mechanisms are reflected in the confounders adjusted for in the analyses. Furthermore, a previous study observed an increased incidence of cancer after MI in patients with heart failure compared to those without heart failure after MI [ 28 ]. Thus, eliminating comorbidities may have eliminated the sicker patients more prone to post-MI heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our data, it is, however, difficult to explain the exact mechanism(s) why the association became insignificant after adjustment for comorbidities, but it may be speculated that environmental factors like tobacco and alcohol [ 25 ], unhealthy diet, shared genetic susceptibility, inflammation [ 26 , 27 ] and medication play a role, since these mechanisms are reflected in the confounders adjusted for in the analyses. Furthermore, a previous study observed an increased incidence of cancer after MI in patients with heart failure compared to those without heart failure after MI [ 28 ]. Thus, eliminating comorbidities may have eliminated the sicker patients more prone to post-MI heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low LVEF was related to non-cardiac death. Poor LV function is suggested to cause cardiac cachexia 20 and may affect systemic immunity 21 , 22 , which leads to non-cardiac deaths such as infection and malignancy. Atrial fibrillation is associated with an increased incidence of cerebrovascular death 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Spoon DB, et al [5] reported an obvious change in the causes of death from cardiac to non-cardiac causes such as cancers, in patients successfully treated with coronary angioplasty for coronary artery diseases. The study by Hasin et al [6] also speculated that heart failure complicated by myocardial infarction is a possible risk for cancers even with a limitation regarding an irregular medical surveillance. Because the SHIP cohort study holds a continuous health survey system for all patients with CVD, we could serve a certain amount of confidence in our observations that a high incidence of cancers is present in patients with atherosclerotic CVD when compared with those with non-atherosclerotic CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide surveillance of health statistics [1] , [2] and/or a large cohort study [3] has critically highlighted the indisputable fact that cardiovascular diseases (CVD), especially atherosclerotic CVD, and cancers are the two leading causes of death among non-communicable diseases irrespective of socioeconomic status. Recent epidemiological studies [4] , [5] , [6] also implied an incremental risk of death due to non-cardiac causes, especially attributable to cancer developments, during the long-term follow-up of patients with coronary artery diseases. Several scientific bodies addressing the pathogenesis of atherosclerotic CVD and/or cancers demonstrated a presence of common denominators such as the role of inflammation [7] , [8] , [9] , [10] , [11] , neovascularity [12] , [13] , epigenetics [14] , [15] , [16] , [17] , [18] , [19] , and lifestyle behaviors [20] , etc., to propose the possible association between both diseases.…”
mentioning
confidence: 99%